THE USE OF SPELLING BEE GAME TO INCREASE THE STUDENTS’ VOCABULARY MASTERY OF THE SEVENTH GRADE AT SMPN I BANTAN - Wan Julia Mayasari (Politeknik Negeri Bengkalis, 2018)
The aim of the study was to find out the effect of using Spelling Bee game on students’ vocabulary mastery before and after being taught by using this game. Simple random sampling was used to determine the sample where 20 students in controlled class and 20 students in experimental class. There were three formulations of the problem: a) How is the students’ vocabulary mastery before being taught by using spelling bee game. b) How is the students’ vocabulary mastery after being taught by using spelling bee game. c) Is there any significant effect by using spelling bee game on students’ vocabulary mastery of the seventh grade at SMPN I Bantan. Based on the result of the test mean score of experimental class was 83, controlled was 67, 5 and ttestwas 6, 18. It showed that ttest is higher than ttablein 1% and 5%(2.02 ≤ 6, 18 ≥ 2.69). It meant that Ha was accepted and Ho was rejected. On the other hand, Spelling Bee Game was effective to increase the students’ vocabulary mastery of the seventh grade at SMPN I Bantan.